Interações ecológicas em Malpighiaceae no cerrado: compartilhamento de guildas de herbívoros e variações nos resultados da interação formiga-planta - Vilela, Andréa Andrade (2010)
Ecological interactions represent essential tools for a better understanding of natural communities, having in animal-plant relationships important models for study. For that, become needful phenological analyses of plants, capable of demonstrating the flowering strategies and with it the ways of temporal organization of resources available for herbivores. The sequential flowering provides with resources consecutively along the year, what favors the sharing of plants for guilds of herbivorous. Herbivores generate negative impacts in the adaptive value of plants, which, in reply, develop defenses such as associations of protection with ants through extrafloral nectaries. However, those relationships represent systems of mutualisms conditioned variations of the environment, capable of presenting results that change from positive to negative on the adaptive value of the interacting species. In the face of that, the present study verified whether the sequential phenology among species of malpighiaceae results in sharing of guilds of herbivores and whether the association with ants is capable of reducing the damage herbivory. The field work was carried out in the cerrado sensu stricto of the Clube de Caça e Pesca Itororó of Uberlandia, Uberlandia/MG, between June 2008 and June 2009, with the species Peixotoa tomentosa, Banisteriopsis laevifolia, Banisteriopsis campestris and Banisteriopsis malifolia. Data on phenology and abundance and richness of ants and herbivores were collected. Moreover, experimental handling in field was carried out, being the control, without ant exclusion, and the treatment, with the ant exclusion for analyses of herbivory. Results have shown that there is sequential flowering among the species that were studied and that the guild of herbivores followed the seasonality in the resources offer of those plants. It is suggested that this flowering strategy has contributed for the guild sharing, since it gives an uninterrupted food supply. The experimental handling has shown ant protection against the foliar herbivory, but there was not protection in the reproductive structures. In that case, it is possible that the temporal variations in the abundance of the main herbivores, as well as behavioral characteristics of herbivores and ants have decreased or eliminated the beneficial effect of ants to the plant productivity. In the case of the P. tomentosa, morphological limitations of ants impeded the thrips (Thysanoptera) were removed from plants, what caused severe damage in reproductive structures. The species B. laevifolia can have been affected by the high abundance of endophytic beetles of the family Curculionidae. In the case of the B. campestris and B. malifolia, it is probable that ant associations with cochineal insects have affected negatively the reproductive success of those species. Phenology results have shown that those plants share guilds of phytophagous insects which use the same types of resources and strategies in the occupation of their niches by acting in a similar way in the ecosystem. With the study of those plant-ant interactions it was possible to show that the protection against herbivores is subjected to the conditionalities of the biotic medium. Thus, the study of how factors influencing the interactions are varying in time and in space becomes fundamental in order to have a better understanding of ecology of multitrophic relationships in natural communities.